Test of impact of vibrations frequency on mean errors of the precise height differences measurement with analogue automatic leveller NI002 = Badanie wpływu częstotliwości drgań na średnie błędy pomiaru przewyższeń w precyzyjnym niwelatorze analogowym NI 002 - Kurnatowski, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the results of tests carried out to determine the measurable effect of vibrations on the accuracy of measurements with an automatic precise leveller. It contains specification of the research station created to examine the case and description of factors affecting the measurement results.
Keywords: vibrations; measurement accuracy; precise levelling; drgania; dokładność pomiaru; niwelacja precyzyjna